ENVIRONMENTAL EMERGENCIES THEIR CLASSIFICATION AND DESCRIPTION. Protection MAKING EVENTS - Meliboyev T.T (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article is devoted to the topic of scientific and practical experience in the study of environmental problems. The article also discusses the types of environmental problems in the world, the causes of their occurrence, environmental and Human Relations, Environmental Protection, the environmental impact of production and industry, environmental policy, and its interstate implementation. Thus, environmental problems lead to a global environmental crisis, which poses a great danger. It is caused by all the myrrh economic activity that causes changes to manifest on a global scale, and these changes are dangerous for the entire population of the planet. You can fight the global environment by reducing pollution to a safe level.